2019
DOI: 10.29303/jpft.v5i1.835
|View full text |Cite
|
Sign up to set email alerts
|

Remediasi Miskonsepsi Peserta Didik Pada Materi Optik Dengan Teknik CRI Modifikasi Melalui Model Learning Cycle 5E

Abstract: This research aimed to find out the level of misconceptions and the effect of 5e learning cycle model. This research was a pre-experimental with pre-test and post-test design. The research population was all of the eleven grade students of Senior High School 1 Mataram consisted of 8 classes. Sampling was done by cluster random sampling technique and obtained students of class XI MIPA 5. Students' misconceptions have been identified by modification of Certainty of Response Index technique and remediated with 5e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
1
0
2
Order By: Relevance
“…Adapun model pembelajaran yang mampu memberikan dampak terhadap penguasaan konsep peserta didik adalah model Learning Cycle 5E (Taufiq, Hindarto, & Khumaedi, 2011;Wicaksono, Wazis, & Madlazim, 2017). Model Learning Cycle 5E telah terbukti efektif untuk digunakan dalam pembelajaran fisika (Khan, Aurangzeb, & Tahir, 2020;Fatimah, 2020;Haeroni, Susilawati, & Rahayu, 2019;Putra et al, 2018;Hartini et al, 2017).…”
Section: Pendahuluanunclassified
“…Adapun model pembelajaran yang mampu memberikan dampak terhadap penguasaan konsep peserta didik adalah model Learning Cycle 5E (Taufiq, Hindarto, & Khumaedi, 2011;Wicaksono, Wazis, & Madlazim, 2017). Model Learning Cycle 5E telah terbukti efektif untuk digunakan dalam pembelajaran fisika (Khan, Aurangzeb, & Tahir, 2020;Fatimah, 2020;Haeroni, Susilawati, & Rahayu, 2019;Putra et al, 2018;Hartini et al, 2017).…”
Section: Pendahuluanunclassified
“…Untuk dapat membelajarkan mahasiswa pada perkuliahan IPA Terpadu yang sifatnya abstrak dan kompleks pada beberapa materi, dibutuhkan model pembelajaran yang efektif dalam meminimalisir miskonsepsi (kesalahpahaman), juga meningkatkan keterampilan berpikir kritis mahasiswa. Salah satu indikator terjadinya miskonsepsi adalah jawaban yang diberikan peserta didik benar akan tetapi peserta didik tidak mampu menjelaskan alasan yang tepat dalam menjawab dan disertai keyakinan yang tinggi akan kebenaran jawaban yang disampaikan (Haeroni et al 2019).…”
Section: Pendahuluanunclassified
“…Sabariasih (2015) also found that remedial teaching can improve learning outcomes in cognitive aspects of students in dynamic fluids materials through the application of Snowball Throwing model on high school students in Surakarta. Moreover, Haeroni, et al (2019) implemented a model of learning cycle in the optics material discovering that remediation is effectively decreasing student misconceptions.…”
mentioning
confidence: 99%